Entrepreneurial Orientation Dimensions, Competitive advantage, and Indonesian F&B SMEs Performance - Parthasarathi, Shrinithy; Ongkowijoyo, Gracia (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research examines the relationship between entrepreneurial orientation and the performance of SMEs within the food and beverage industry in East Java – Indonesia. With the help of an online survey, data were gathered from 105 participants using a structured questionnaire adopting an exploratory quantitative research design. These highlights indicate that many respondents are mature business people, with over 50% being 36 years and above. The study reveals that F&B remains the fastest-growing sector, with an average annual growth rate of 5.33% after COVID-19. The findings of the study show that the element of entrepreneurial orientation has the most significant impact on the firm competitiveness and performance. This research adds to the literature on how these businesses can effectively manage environmental changes and adjust to new opportunities and threats. The findings indicate that educating SME owners about entrepreneurship would enhance the businesses’ performances and sustainability in the F&B market